Direct identification of potato's fungal phyto-pathogens by Fourier-transform infrared (FTIR) microscopy. Issue 6 (2010) - Erukhimovitch, V.; Tsror (Lahkim), L.; Hazanovsky, M.; Huleihel, M.
Abstract : Fungi are considered as serious pathogens to many plants and can cause a severe economic damage. The available methods for identification of fungi are time consuming and not always very specific. In the present study we examined the potential of FTIR microscopy for direct detection and identification of different fungal potato pathogens on the surface of potato tubers. Unique spectral bands for each of the examined fungal pathogens appeared in the spectra of naturally infected potatoes. These results strongly support the potential of FTIR microscopy for successful detection and probably discrimination between different fungal pathogens directly from the infected tissue.